Stereoscopic objects affect reaching performance in virtual reality environments: influence of age on motor control - Kim, Hyeonseok; Kim, Yeongdae; Lee, Jongho; Kim, Jaehyo (Frontiers in Virtual Reality, 2024)
Although the stereoscopic effect in 3D virtual reality (VR) space has been studied, its influence on motor performance, specifically how stereoscopic objects affect behavioral outcomes like reaching, remains unclear. Previous research has primarily focused on perceptual aspects rather than on how stereoscopic visual input impacts motor control at the behavioral level. Thus, we investigated the effects of stereoscopic objects in a VR environment on reaching performance, examining whether the stereoscopic effect of objects is a significant aspect enough to affect performance at the behavioral level. While doing so, we investigated young and older adults separately, as age is a critical factor influencing motor performance. Fourteen young and 23 older participants performed a reaching task in the VR space. The target objects were 2D and 3D, deviating from the initial position by 10 and 20 cm. The movement attributed to feedforward control was analyzed using end-point error and smoothness of movement. Our results revealed that older participants had significantly worse predictive control than young participants in the 3D long task, suggesting that the positions of 3D objects were more difficult to predict than those of 2D objects. Young participants showed a significant difference in smoothness between 2D and 3D objects, which was not observed in older participants. This may reflect the floor effect in older participants. Under the short-distance condition, neither group showed a significant difference, suggesting the ceiling effect by distance. We confirmed that the effect of stereoscopic objects was not drastic but it did hamper the reaching performance.